Expression analyses of cave mollies (Poecilia mexicana) reveal key genes involved in the early evolution of eye regression. (23rd October 2019) - McGowan, Kerry L.; Passow, Courtney N.; Arias-Rodriguez, Lenin; Tobler, Michael; Kelley, Joanna L.
Abstract : Eye regression occurs across cave-dwelling populations of many species and is often coupled with a decrease or loss in eye function. Teleost fishes are among the few vertebrates to undergo widespread colonization of caves and often exhibit eye regression with blindness. Cave populations of the poeciliid fish Poecilia mexicana (cave molly) exhibit reduced—albeit functional—eyes, offering the opportunity to investigate partial eye regression. We sequenced eye transcriptomes of cave and surface populations of P. mexicana to identify differentially expressed genes that potentially underlie eye regression in cave mollies. We identified 28 significantly differentially expressed genes, 20 of which were directly related to light sensitivity, eye structure and visual signaling. Twenty-six of these genes were downregulated in cave compared to surface populations. Functional enrichment analysis revealed eye-related gene ontologies that were under-represented in cave mollies. In addition, a set of co-expressed genes related to vision and circadian rhythm was correlated with habitat type (cave versus surface). Our study suggests that differential gene expression plays a key role in the beginning evolutionary stages of eye regression in P. mexicana, shedding further light on regressive evolution in cavefish.